The Effectiveness of Guided Inquiry Learning Model on Students’ Scientific Literacy Skills: A Literature Review (2016-2025) - Asyil Arifah; Eldza Rosmiatin Nafiz; Shelliana Iqlima (Indonesian Publication Center, 2026)
This study aims to analyze and identify the effectiveness of the guided inquiry learning model on students' scientific literacy skills during the 2016–2025 period. The method used is a literature review with a qualitative descriptive approach involving 20 relevant national journal articles. The analysis process was carried out through the stages of identification, selection, and synthesis of research findings. The results of the review indicate that the guided inquiry learning model consistently has a positive and significant effect on improving students' scientific literacy. These improvements include aspects of conceptual understanding, analytical skills, interpretation of scientific data, as well as critical thinking and problem-solving skills. The strength of this model lies in students’ active involvement in a structured scientific investigation process, making learning more meaningful. Therefore, the guided inquiry learning model is recommended as an effective alternative science learning strategy to enhance students' scientific literacy and support the development of 21st-century skills.